2022
DOI: 10.32620/reks.2022.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis and prediction of polarity vaccines based on Twitter data using deep NLP techniques

Abstract: The global impact of COVID-19 has been significant and several vaccines have been developed to combat this virus. However, these vaccines have varying levels of efficacy and effectiveness in preventing illness and providing immunity. As the world continues to grapple with the ongoing pandemic, the development and distribution of effective vaccines remains a top priority, making monitoring prevention strategies mandatory and necessary to mitigate the spread of the disease. These vaccines have raised a huge deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…An unsupervised neural language model is used to train word embedding and is trained by an unsupervised group of tweets. The conventional neural network is used to refine the embedding on the supervised corpus [10]. The components used in the proposed work are activations, sentence matrix pooling, SoftMax and convolutional layer [11].…”
Section: Research Objectivesmentioning
confidence: 99%
“…An unsupervised neural language model is used to train word embedding and is trained by an unsupervised group of tweets. The conventional neural network is used to refine the embedding on the supervised corpus [10]. The components used in the proposed work are activations, sentence matrix pooling, SoftMax and convolutional layer [11].…”
Section: Research Objectivesmentioning
confidence: 99%
“…Topic modeling is essential to comprehend the tweets and group them into manage-able categories. As traditional methodologies are unable to effectively handle noise, high volume, dimensionality, and short text sparseness, some authors [10] rely on topic modelling approaches to cluster the tweets (or short text messages) to groups. Their original solution uses a hierarchical two-stage clustering technique and can address the problem of data sparsity in short text.…”
Section: Society and Political Views (Elections) And Other Subjects R...mentioning
confidence: 99%
“…However, because tweets are limited to 280 characters, individuals tend to use casual language, which makes it difficult to understand the true mood behind tweets [8]. Also, due to the high number of total registered users (650 million) and instant notifications [9], [10] over a broad range of mobile equipment's, Twitter provide useful datasets for research to help better understand public behaviors, opinions, and sentiments [11]. This review is built on Social Media (SM) datasets where Twitter/X was found to be the most prominent for many reasons, such as: high data volume, public data availability, hashtags (relevant for clustering analysis), text-based posts, real-time analysis and abundant recent publications which are conducive to performing a comprehensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The NLP methods provide a wide variety of possibilities for data extraction from natural language texts. A good example is paper [2], which describes the application of NLP prognostic analytics aimed at the extraction of certain text entities from twits regarding the evaluation of comments polarity on vaccine quality. This study utilizes the Apache Spark Framework app., which gives the possibility to process significant amounts of data using the distribution method.…”
Section: Analysis Of Work Related and Objectivesmentioning
confidence: 99%